Risk factors for postpartum haemorrhage in women with histologically verified placenta accreta spectrum disorders: a retrospective single-centre cross-sectional study - Naghmeh Ghaem Maghami; Fabrice Helfenstein; Gwendolin Manegold-Brauer; Gabriela Amstad (BMC, 2023)
Abstract Background Placenta accreta spectrum (PAS) disorders have been reported with an increasing frequency of up to 3%. The increase in the incidence can be explained by the rising rate of Caesarean section (CS), assisted reproductive technology (ART) and previous uterine surgeries. PAS disorders are usually associated with postpartum haemorrhage (PPH). In our study, we investigated the risk factors for increased blood loss in women with histologically verified PAS disorders independent of delivery mode. Methods In a retrospective single-centre cross-sectional study, 2,223 pregnant women with histologically verified PAS disorders were included. Risk factors for PPH in women with PAS disorders were examined and compared between women with PPH (study group; n = 879) and women with normal blood loss (control group; n = 1150), independent of delivery mode. PAS disorders were diagnosed histologically from the following specimens: placenta, placental-bed specimens, uterine curettage, uterine resection and/or total/partial hysterectomy. Medical data were extracted from clinical records of pregnant women with PAS disorders delivering at the University Hospital Basel between 1986 and 2019. The placenta data of women with PAS disorders were obtained and identified through a search from the database of the Department of Pathology, University Hospital Basel. Results Between 1986 and 2019, there were 64,472 deliveries at the University Hospital Basel. PAS disorders were histologically verified in 2,223 women (2,223/64,472), and the prevalence of PAS disorders was 3.45%. A total of 879 women with PAS disorders showed PPH, independent of delivery mode (43.3%). Due to missing data for 194 women, the final analysis was conducted with the remaining 2,029 women. Placenta praevia (O.R. = 6.087; 95% CI, 3.813 to 9.778), previous endometritis (O.R. = 3.011; 95% CI, 1.060 to 9.018), previous manual placenta removal (O.R. = 2.530; 95% CI, 1.700 to 3.796), ART (O.R. = 2.169; 95% CI, 1.593 to 2.960) and vaginal operative birth (O.R. = 1.715; 95% CI, 1.225-2.428) can be considered important risk factors, and previous CS (O.R. = 1.408; 95% CI, 1.016 to 1.950) can be considered a moderate potential risk factor of PPH in women with PAS disorders. Conclusions Placenta praevia, previous endometritis, previous placenta removal, ART and vaginal operative birth can be considered important risk factors of PPH in women with PAS disorders. Study registration The study was registered under http://www.ClinicalTrials.gov (NCT05542043) on 15 September 2022.